Genome-Wide Analysis and Expression Profiles of Ethylene Signal Genes and Apetala2/Ethylene-Responsive Factors in Peanut (Arachis hypogaea L.) - Cui, Yuanyuan; Bian, Jianxin; Guan, Yu; Xu, Fangtao; Han, Xue; Deng, Xingwang; Liu, Xiaoqin (Frontiers in Plant Science, 2022)
Peanut is an important oil and economic crop widely cultivated in the world. It has special characteristics, blooming on the ground but bearing fruits underground. During the peg penetrating into the ground, it is subjected to mechanical stress from the soil at the same time. It has been proved that mechanical stress affects plant growth and development by regulating the ethylene signaling related genes. In this study, we identified some genes related ethylene signal of peanut, including 10 ethylene sensors, 2 CTRs, 4 EIN2s, 4 EIN3s, 6 EBFs and 188 AP2/ERFs. One hundred and eighty-eight AP2/ERFs were further divided into four subfamilies, 123 ERFs, 56 AP2s, 6 RAVs and 3 Soloists，of them one hundred and seventy AP2/ERF gene pairs were clustered into segmental duplication events in genome of Arachis hypogaea. A total of 134, 138, 97 and 150 AhAP2/ERF genes formed 210, 195, 166 and 525 orthologous gene pairs with Arachis duranensis, Arachis ipaensis, Arabidopsis thaliana and Glycine max, respectively. Our transcriptome results showed that 2 EIN3s (Arahy.J729H0 and Arahy.S7XF8N) and 1 EBFs (Arahy.G4JMEM) were highly expressed when mechanical stress increased. Among the 188 AhAP2/ERF genes, there were 31 genes with the FPKM ≥ 100 at least one of the 15 samples of Tifrunner. Among them, 3 AhAP2/ERFs (Arahy.15RATX, Arahy.FAI7YU and Arahy.452FBF) specifically expressed in seeds and 5 AhAP2/ERFs (Arahy.HGAZ7D, Arahy.ZW7540, Arahy.4XS3FZ, Arahy.QGFJ76 and Arahy.AS0C7C) highly expressed in the tissues which responded mechanical stress, suggesting that they might sense mechanical stress. Mechanical stress simulation experiment showed that 3 AhAP2/ERFs (Arahy.QGFJ76, Arahy.AS0C7C and Arahy.HGAZ7D) were sensitive to mechanical stress changes and they all had the conservative repressor motif (DLNXXP) in the C-terminus, indicated they might transmit mechanical stress signals through transcriptional inhibition. Our study reveals the regulatory landscape of ethylene signal related genes in peanut, providing valuable information for the mining of target genes for further study.